An interesting case of lip swelling! - Evelyn Yap Wen Yee (Academy of Family Physicians of Malaysia, 2021)
Melkersson-Rosenthal Syndrome (also termed “Miescher-Melkersson-Rosenthal Syndrome”) or (MRS), is a rare neurocutaneous disorder characterized by the clinical triad of recurring facial nerve paralysis, swelling of one or both lips and fissural tongue. We report a patient with Melkersson-Rosenthal Syndrome initially referred to Dermatology Department as angioedema. The diagnosis and treatment procedures were presented with special emphasis to the clinical features of this rare condition.